(untitled) (Ameghiniana, 2013)
The characteristics of an important set of arborescent lycphytes found the Upper Paleozoic sedimentary rocks of the Cerro Agua Negra Formation are described in this paper. The lycphytes moulds were found in their growth position, reaching 60 cm in diameter. lts preservation does not allow a determination for a precise systematic position. Some impressions, similar to those known as Lycopodiopsis in the paleobotanic literature were collected in the same layers. This material has a special paleoenvironmental interest since the layers bearing the fossil material show episodes of subaerial deposition on alluvial plains or interdistributary bays. Likewise, the paleomagnetic data suggest a paleolatitude near 2sD for the location where the lycophytes moulds were found. This information agrees with the anatomic characteristic of these plants, which could not support periglacial conditions with a permafrost.